Predictores de dolor anterior de rodilla en pacientes operados de artroplastia total de rodilla sin reemplazo patelar - Barahona V., Maximiliano; Barrientos M., Cristián; Barahona V., Macarena; Guzmán G., Mauricio; Ramírez P., Marcela (Revista Hospital Clínico Universidad de Chile, 2022)
Osteoarthrosis of the knee is one of the most important causes of disability around the world, being total knee arthroplasty (TKA) a cost-effective surgical procedure for treating its severe stage when all knee compartments are compromised. Despite the good functional results and good survival of the implants and of the patients, still, 15 to 20% of the patients are dissatisfied after surgery. One of the causes of dissatisfaction is persistent pain located in the anterior part of the knee, which leads to controversy over whether to perform the patellar replacement. Advantages and complications are described in both scenarios, and neither is superior to the other in pain and implant survival. In the case of TKA without patellar replacement, the position of the femoral component plays a crucial role in achieving normal patellar tracking. The current challenge is to determine those clinical and radiological variables that allow us to predict the absence of long-term anterior pain in patients who require TKA and who do not undergo patellar replacement.